Spectral band configuration for airborne hyperspectral imaging of tropical forest. - Nuruddin, Ahmad Ainuddin; Suhaili, Affendi; Okkonen, Jukka; Mariappan, Manohar; Mohd. Shafri, Helmi Zulhaidi; Nioor, Awang; Ibrahim, Faridah Hanum (2009)

(untitled)
A product incorporating the spectral configuration for airborne hyperspectral imaging application of the tropical forests, which are derived from multivariate procedures and accommodated to the programmable AISA sensor system. In situ spectral data sets were used in determination of the spectral band locations and bandwidths by applying the stepwise discriminant analysis (SDA) and hierarchical clustering (HC) procedures. The final spectral configuration were determined based on 3-piece linear fitting to match the wavelength range and spectral channels that is defined by the spectral sampling of the base wavelength regions in the sensor system file.